Customer Loyalty of Export Loss Insurance In South Sulawesi - Nasir, Amron Ahmad (MEDIA EKONOMI & TEKNOLOGI INFORMASI, 2013)
This study aims to analyze the influence of product quality, agent competency and company trust to the customers loyaltyof export loss insurance in South Sulawesi, Indonesia.